A novel gene mutation in ZP3 loop region identified in patients with empty follicle syndrome. Issue 2 (19th December 2021) - Zhang, Zhiqiang; Guo, Qi; Jia, Lei; Zhou, Chuanchuan; He, Shujing; Fang, Cong; Zhang, Minfang; Sun, Peng; Zeng, Zhi; Wang, Meng; Wang, Dandan; Liang, Xiaoyan
Abstract: The zona pellucida (ZP) is an extracellular matrix surrounding mammalian oocytes. It is composed of three to four glycoproteins, ZP1–ZP4 . ZP3 is essential for sperm binding and zona matrix formation. Here, we identified a novel heterozygous mutation (NM_001110354.2:c.502_504delGAG) of ZP3, occurring in a pair of sisters with empty follicle syndrome (EFS). A mouse model with the same mutation was established using the CRISPR/Cas9 gene‐editing system. As in the above family, F0 ‐, F1 ‐, and F2 ‐generation female mice with the mutation were all infertile. Further analysis using the Chinese hamster ovary cells (CHO‐K1) also showed that this mutation weakens the strength of binding between ZP3 and ZP2, which hinders the assembly of ZP and results in unstable ZP formation. Immunohistochemical analysis using ovarian serial sections in both humans and mice demonstrated that the ZP of preantral follicles was thinner than normal control, or even absent. Our study presents a new gene mutation that leads to EFS, providing new evidence and support for the genetic diagnosis of infertile individuals with similar phenotypes. Our results also show that the loop of ZP3 is not only a linker between two amphiphilic helices but may play a critical role in specifying the correct heterodimerization partner. Abstract : We identified a novel heterozygous mutation in ZP3 loop region causes deletion of the 168th glutamic acid and further leads to empty follicle syndrome. This mutation weakens the strength of binding between ZP3 and ZP2, which hinders the assembly of ZP and results in a thinner ZP than normal control, or even absent. In the light microscopy, the oocytes ZP in mutant female mice were not observed and avoid polyspermy fertilization. Some of them even collapsed.